The Allowable Time Approach of the Uncertain Task for Three U-shaped Lines with the Minimum Workstations - Suthep Varnasilpin; Ruedee Masuchun (My University, 2019)
UL (U-shaped Line) reduces the waste material in a manufacturing process.This paper presents the application of three U-shaped Lines with the minimum workstations which consists of UL-1, UL-2, and UL-3.The uncertain task of three U-shaped Lines determines the time as an interval.Three U-shaped Lines formulate the model with a binary integer linear programming.Each uncertain task reduces the normal time to the optimism time.The normal time reduction relates to the allowable time inversely.This paper indicates the procedure of the normal time reduction that applies MATLAB R2014a.The allowable time of UL-1, UL-2, and UL-3 for each uncertain task is 1.5 times of the optimistic time, 1.2 times of the optimistic time, and 1 time of the most optimistic time, respectively.For the utility of this paper, the uncertain task adjusts the finish time which does not affect the modification of the minimum number of workstations.
Keywords: Workstation; Line (geometry); Assembly Line Balancing Optimization